2009
DOI: 10.3796/ksft.2009.45.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Size selectivity of gill net for female snow crab, Chionoecetes opilio

Abstract: A series of fishing experiments was carried out in the eastern coastal waters of Korea from January, 2002 to March, 2003, using gill nets of different mesh sizes (m 180, 210, 240, 270 and 300 mm) to determine the size selectivity of gill net for female snow crab, Chionoecetes opilio. The catch of experimental gears was mostly snow crab (97%), Chionoecetes opilio. The maximum carapace length (RL) of each female snow crab caught in the fishing experiments was measured. The master selection curve was estimated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…al., 2004;Millar and Walsh, 1992;Kim et al, 2012) 등이 사용되고 있다. 본 연구에 서는 어획 대상 생물인 꽃게가 망지에 얽혀서 어 획되는 특성을 고려하여 Kitahara 방법을 사용하 여 망목 선택성을 분석하였다 (Fujimori et al, 1996;Cho et al, 2000;Park et al, 2003;Park et al, 2009, Kim et al, 2010 Kitahara, 1968;Park et al, 2003;Park et al, 2011). Fujimori et al, 1996;Park et al, 2003;Jo et al, 2006).…”
Section: 망목 선택성 곡선 추정법unclassified
“…al., 2004;Millar and Walsh, 1992;Kim et al, 2012) 등이 사용되고 있다. 본 연구에 서는 어획 대상 생물인 꽃게가 망지에 얽혀서 어 획되는 특성을 고려하여 Kitahara 방법을 사용하 여 망목 선택성을 분석하였다 (Fujimori et al, 1996;Cho et al, 2000;Park et al, 2003;Park et al, 2009, Kim et al, 2010 Kitahara, 1968;Park et al, 2003;Park et al, 2011). Fujimori et al, 1996;Park et al, 2003;Jo et al, 2006).…”
Section: 망목 선택성 곡선 추정법unclassified
“…Gillnets work in the following three ways: sticking, entangling and confining the gills of the target species into the net. Gillnet gear is widely used to identify the species and length characteristics of catches [4][5][6][7][8][9][10][11][12][13]. Furthermore, gillnet materials and fishing methods differ depending on the country, region, and target species.…”
Section: Introductionmentioning
confidence: 99%
“…In blackfin flounder fishery, tie-down gillnet with different mesh sizes could be reduce the bycatch of the immature flounders and the research on mesh size selectivity in trammel nets were conducted for 17 species in the Atlantic oceans; however, their performance is unclear while further studies are still needed in different areas and methods (An et al, 2003;He, 2006;Park and Bae, 2017;KOSIS, 2020). Recently, researches were conducted on selectivity as a function of different mesh sizes (Cho et al, 2000;Park et al, 2003;Haas, 2010). It was reported that the fishing performance of gillnets varies depending on the stretched height of the net between the float line and the foot rope, mesh size selectivity and that the shape of gillnets (e.g.…”
Section: Introductionmentioning
confidence: 99%